Yeast diversity isolated from grape musts during spontaneous fermentation from a brazilian winery - Bezerra-Bussoli, Carolina [UNESP]; Baffi, Milla Alves; Gomes, Eleni [UNESP]; Da-Silva, Roberto [UNESP] (Springer Nature, 2013)
Saccharomyces and non-Saccharomyces yeast species from a winery located in Brazil were identified by ribosomal gene-sequencing analysis. A total of 130 yeast strains were isolated from grape surfaces and musts during alcoholic fermentation from Isabel, Bordeaux, and Cabernet Sauvignon varieties. Samples were submitted to PCR-RFLP analysis and genomic sequencing. Thirteen species were identified: Candida quercitrusa, Candida stellata, Cryptococcus flavescens, Cryptococcus laurentii, Hanseniaspora uvarum, Issatchenkia occidentalis, Issatchenkia orientalis, Issatchenkia terricola, Pichia kluyveri, Pichia guilliermondii, Pichia sp., Saccharomyces cerevisiae, and Sporidiobolus pararoseus. A sequential substitution of species during the different stages of fermentation, with a dominance of non-Saccharomyces yeasts at the beginning, and a successive replacement of species by S. cerevisiae strains at the final steps were observed. This is the first report about the yeast distribution present throughout the alcoholic fermentation in a Brazilian winery, providing supportive information for future studies on their contribution to wine quality. © 2013 Springer Science+Business Media New York.
Keywords: Brazil; Candida quercitrusa; Candida stellata; controlled study; Cryptococcus flavescens; Cryptococcus laurentii; fermentation; fungal strain; fungus isolation; gene sequence; grape must; Hanseniaspora uvarum; Issatchenkia occidentalis; Issatchenkia orientalis; Issatchenkia terricola; nonhuman; nucleotide sequence; Pichia guilliermondii; pichia kluyveri; polymerase chain reaction; priority journal; restriction fragment length polymorphism; Saccharomyces cerevisiae; sequence analysis; species distribution; species diversity; Sporidiobolus pararoseus; wine industry; yeast; Pichia kluyveri; Pichia sp.; Saccharomyces; Vitaceae